Enzyme feeding strategies for better fed-batch enzymatic hydrolysis of empty fruit bunch. (May 2016) - Sugiharto, Yohanes Eko Chandra; Harimawan, Ardiyan; Kresnowati, Made Tri Ari Penia; Purwadi, Ronny; Mariyana, Rina; Andry; Fitriana, Hana Nur; Hosen, Hauna Fathmadinda
Highlights: It is important to decide enzyme feeding method for enzymatic hydrolysis. If enzymatic hydrolysis is run less than 40 h, whole enzyme feeding is preferable. If enzymatic hydrolysis is run more than 40 h, proportional enzyme feeding is preferable. Abstract: Lignin inhibitory becomes a major obstacle for enzymatic hydrolysis of empty fruit bunch conducted in high solid loading. Since current technology required high enzyme loading, surfactant application could not effectively used since it is only efficient in low enzyme loading. In addition, it will increase final operation cost. Hence, another method namely "proportional enzyme feeding" was investigated in this paper. In this method, enzyme was added to reactor proportionally to substrate addition, different from conventional method ("whole enzyme feeding") where whole enzyme was added prior to hydrolysis process started. Proportional enzyme feeding could increase enzymatic digestibility and glucose concentration up to 26% and 12% respectively, compared to whole enzyme feeding for hydrolysis duration more than 40 h. If enzymatic hydrolysis was run less than 40 h (25% solid loading), whole enzyme feeding is preferable.